Shedding light on the impact of a dissolution-precipitation recycling process on crystallization and thermal stability of PBS - Lahfaidh, Fakhri-Eddin N.; Guigo, Nathanael; Vincent, Luc; Sbirrazzuoli, Nicolas (Polymer testing, 2025)
Poly(butylene succinate) (PBS) was recycled via dissolution/precipitation using Cyrene as a green solvent. The PBS recyclates were characterized by SEC, NMR, FTIR and TGA. The recycling process selectively removed the most polar chains and increased the proportion of shorter chains (lower Mn), as determined by size exclusion chromatography (SEC). Nuclear magnetic resonance (NMR) and infrared (IR) spectroscopy confirmed a reduction in -OH end groups alongside an increase in -CH3 end groups, indicating a slight decrease in polarity. This selective chain alteration significantly improved crystallization, as demonstrated by advanced kinetic analyses and Hoffman-Lauritzen (HL) theory. A lower energy barrier to nucleation (Kg) for recycled PBS (rPBS) highlighted an enhanced nucleation process, facilitating earlier crystallization during both heating and cooling, despite reduced diffusion. The recycled chains achieved favorable positioning more readily, influenced by entropic effects rather than the energetic barriers typically encountered during heating. This observation was further supported by higher pre-exponential term values in HL's equation for rPBS. Moreover, the pronounced crystallization differences during cooling were attributed to the low Kg values, emphasizing nucleation as the primary driving force. Ultimately, the formation of shorter chains and reduced polarity in rPBS were identified as key contributors to enhanced nucleation. Temperature-Modulated DSC (TOPEM) confirmed a structural heterogeneity inside the recycled sample. The thermal stability of both polymers was investigated, showing increased degradation at lower heating rates for rPBS, while being comparable to the fresh product at higher rates. Degradation mechanisms were studied using isoconversional kinetics, and showed major differences from 310 to 370 °C. [Display omitted] •A selective dissolution/precipitation method using Cyrene ™ is presented to recycle PBS.•Recycling decreases polar chains number and increases molecular weight distribution.•Removal of these chains enhanced crystallization after recycling.•HL theory and advanced kinetics confirmed enhanced nucleation for rPBS.•Different thermal resistance and degradation mechanisms observed at high heating rates.